Technical Efficiency of Organic Rice Farming Under Environmental Uncertainty: A Stochastic Frontier Analysis - Antonio Brian Deeng; Hasbiadi Hasbiadi; Campina Illa Prihantini (Universitas Galuh, 2026)
Technical efficiency constitutes a critical indicator in evaluating the overall effectiveness of farming systems. Within the context of organic rice cultivation, farmers are generally required to employ a wider range of tools and inputs compared to their conventional counterparts. These practices encompass the application of organic fertilizers, the adoption of natural pest management strategies, and the implementation of environmentally sustainable cultivation techniques. The primary objective of this study is to assess the efficiency levels of farmers in responding to environmental uncertainties, thereby providing an empirical foundation for improvements in farm management and the formulation of sustainable agricultural policies. The findings reveal that 40% of organic rice farmers in Kolaka Regency did not experience production disruptions during periods of climatic uncertainty, even in the absence of supplementary inputs such as pesticides and synthetic fertilizers—inputs that typically contribute to escalating production costs in conventional farming systems. This evidence underscores the resilience of organic farming practices to climate variability. The study employed the Stochastic Frontier Analysis (SFA) method, drawing on a sample of 40 organic rice farmers in Kolaka Regency, and offers valuable insights for policy development aimed at strengthening sustainable agriculture in the region.